1990
DOI: 10.1103/physrevlett.64.204
|View full text |Cite
|
Sign up to set email alerts
|

New high-pressure phase transition in zirconium metal

Abstract: Phase transitions in the group-IV transition metal zirconium were studied by the energy-dispersive xray-diffraction technique with a synchrotron source to a pressure of 32 GPa. A first-order phase transition between an co phase and a bcc phase (isostructural with group-V transition elements) was observed during compression and decompression in a pressure range of 30 ± 2 GPa, which is in qualitative agreement with the recent first-principles theoretical predictions. The observation of the bcc phase in Zr (a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
112
4
3

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(131 citation statements)
references
References 15 publications
12
112
4
3
Order By: Relevance
“…The reported intermediate orthorhombic  phase (transforming between ~ 116 GPa -128 GPa) possessed a distorted hcp crystal structure (space group Cmcm), and the orthorhombic  phase (transforming at ~ 145 GPa) was of a distorted bcc type structure (space group Cmcm) (Akahama et al, 2001). These observations for Ti are at variance with the other Titanium Group transition metals Zr and Hf, which have been observed to follow the     pathway at RT (Jayaraman et al, 1963;Xia et al, 1990a;Xia et al, 1990b). However, Ahuja et al have observed the coexistence of a bcc-like structure (referred to by the authors as ') with the ω phase, during the compression of Ti at RT from 40 GPa to 80 GPa (Ahuja et al, 2004).…”
Section: Room Temperature Compressioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The reported intermediate orthorhombic  phase (transforming between ~ 116 GPa -128 GPa) possessed a distorted hcp crystal structure (space group Cmcm), and the orthorhombic  phase (transforming at ~ 145 GPa) was of a distorted bcc type structure (space group Cmcm) (Akahama et al, 2001). These observations for Ti are at variance with the other Titanium Group transition metals Zr and Hf, which have been observed to follow the     pathway at RT (Jayaraman et al, 1963;Xia et al, 1990a;Xia et al, 1990b). However, Ahuja et al have observed the coexistence of a bcc-like structure (referred to by the authors as ') with the ω phase, during the compression of Ti at RT from 40 GPa to 80 GPa (Ahuja et al, 2004).…”
Section: Room Temperature Compressioncontrasting
confidence: 46%
“…The observation of the   ω  transformation pathway at RT for Ti-6Al-4V suggests that the slope of the -phase boundary (see boundary in figure 2) is negative at high pressures, or that there are two separate areas of phase separated by the  phase (see for example, Xia, 1990a).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…All of these facts indicate that pressure is a key issue for the formation of an amorphous phase from a pure metal. Moreover, we notice that the amorphous phase of Zr is produced in a pressure-temperature range close to the triple point at about 5.5 GPa and 700 C in the phase diagram of Zr [19][20][21]. The amorphization of elemental Zr could be explained in the following way.…”
mentioning
confidence: 99%
“…On static volume compression, Ti does not follow the α → ω → β transformation sequence predicted for, and observed in, both Zr and Hf [9][10][11][12] . The transition to the ω-phase occurs at 3-9 GPa on pressure increase [13][14][15][16][17][18] , and the ω-phase can be retained as a metastable phase at ambient pressure; the reverse transition back to the α phase in Ti occurs only on heating for extended periods at 380 K 13 .…”
mentioning
confidence: 99%